1991
DOI: 10.1063/1.459834
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cluster ions produced by the sputtering or direct laser vaporization of group 13 metal (Al, Ga, and In) oxides

Abstract: The stabilities and reactivities of cluster ions generated from the fast-atom bombardment (FAB) or the direct laser vaporization (DLV) of the Group 13 metal oxides (Al2O3, Ga2O3, and In2O3) were examined by mass spectrometry. The nascent cluster ion distributions, fragmentations, and reactions were studied. The observed patterns of stability and reactivity were compared with the structures and heats of formation calculated from theoretical studies of aluminum oxide cluster ions using MNDO, Xα, and Born–Mayer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…9 Small clusters of gallium oxide can be considered a prototype model to understand the physics and chemistry of nanostructures. A few scattered studies have been reported on gallium oxide at the cluster level including monomer, 10,11 triatomic, 12,13 and dimer [14][15][16][17] clusters. Recently, we initiated a systematic study of the evolution of the physical and chemical properties of small gallium oxide clusters to determine their convergence to the corresponding bulk values.…”
Section: Introductionmentioning
confidence: 99%
“…9 Small clusters of gallium oxide can be considered a prototype model to understand the physics and chemistry of nanostructures. A few scattered studies have been reported on gallium oxide at the cluster level including monomer, 10,11 triatomic, 12,13 and dimer [14][15][16][17] clusters. Recently, we initiated a systematic study of the evolution of the physical and chemical properties of small gallium oxide clusters to determine their convergence to the corresponding bulk values.…”
Section: Introductionmentioning
confidence: 99%
“…First, the formation of Al 2 O + from Al 2 + was examined. Figure 3 shows mass spectra of product ions upon reaction of Al 40 and cationic 29,41 Al 2 O x H y clusters. The rhombic structure is also found in bulk α-Al 2 O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Al 2 O 2 has been detected mass spectrometrically in the vapor over alumina [41,42]. It is a product of the reactions of pulsed-laser evaporated aluminum atoms with molecular oxygen [36].…”
Section: Aluminum Oxidesmentioning
confidence: 99%